Considerations Underlying Technology and Engineering Vocational School Teachers in Choosing Problem-Based Learning Strategies - Rusmono Rusmono; Wisnu Djatmiko (International Journal of Education, Information Technology, and Others, 2021)
This study aims to determine the considerations that underlie Vocational High School (SMK) technology and engineering teachers in choosing the Problem Based Learning (PBL) strategy. The survey measured teachers' perceptions in practicing PBL, the value of PBL implementation for teachers, the value of PBL implementation for students, PBL implementation costs, perceptions of teacher autonomy in implementing PBL, and perceptions of teacher support for their PBL implementation. A total of 94 teachers have confidence in their professional development with PBL strategies, compared to 24 teachers who do not have the competence and confidence in implementing PBL strategies. The findings in this study are the need for the development of formal PBL strategy pedagogical competencies in building understanding and confidence of technology and engineering vocational school teachers. It is recommended that teachers who have experience share their experiences in implementing PBL strategies to encourage student learning achievement.